Spatio-Temporal Analysis of Rainfall Variability and its Prediction in Al-Qassim Region Using (1987-2017) - Alturki, Aljazy Khalid; Aldughairi, Ahmad Abdullah (Journal of natural sciences, life and applied sciences, 2020)
This study aimed to analyze the indicators of spatial and temporal distribution of daily, monthly, and seasonal rainfall measurements. It is looking for the possibility of the stability or change of precipitation properties by using the data of the present. Also, it is working with the most important factors that effects on the rainfall, Moreover, many of some statistical methods applied in this study. Using inverted distance weighted Inverse Distance Weighting (IDW) method to generates rain interpolation surface that is tool approves in geographic information systems software.Rain is an important element of many economic activities. Therefore, the importance of predicting the spatial distribution of precipitation that is important from water rain resources. This study presents an analysis of spatiotemporal variation of the daily, monthly and seasonal rainfall in Qassim region, based on data seven weather stations, that is including, Buraidah, Unaizah, Al Rasa, and the General Authority for Meteorology and Environmental Protection, also Prince Nayef Airport Station between (2017-1987) which period included 31 years for the accuracy of the results.The study reached to several recommendations that can be used in geographical fields, whether environmental or human, which are related to water resources and torrents, rainwater drainage projects and urban areas to avoid disasters.
Keywords: variance; Precipitation probability; Inverted weighted distance method